2017
DOI: 10.1096/fj.201601381r
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system activation mediates the increase in whole‐body glucose uptake in response to electroacupuncture

Abstract: A single bout of low-frequency electroacupuncture (EA) causing muscle contractions increases whole-body glucose uptake in insulin-resistant rats. We explored the underlying mechanism of this finding and whether it can be translated into clinical settings. Changes in glucose infusion rate (GIR) were measured by euglycemic-hyperinsulinemic clamp during and after 45 min of low-frequency EA in 21 overweight/obese women with polycystic ovary syndrome (PCOS) and 21 controls matched for age, weight, and body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Moreover, acupuncture could promote ovulation in women with PCOS, and improve follicle development by decreasing AMH expression to regulate FSH and AMH in granulosa cells 20,21 . In addition, an animal model confirmed the effect of acupuncture was, at least in part, medicated by decreasing sympathetic nerve activity 22 .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, acupuncture could promote ovulation in women with PCOS, and improve follicle development by decreasing AMH expression to regulate FSH and AMH in granulosa cells 20,21 . In addition, an animal model confirmed the effect of acupuncture was, at least in part, medicated by decreasing sympathetic nerve activity 22 .…”
Section: Introductionmentioning
confidence: 79%
“…Clinical studies have indicated that acupuncture can increase menstrual frequency, promote ovulation, decrease testosterone levels, and improve insulin sensitivity in women with PCOS 20,23,33 . Moreover, animal studies verified that acupuncture could promote normal reproduction and alleviate metabolic disorder of PCOS, at least in part, mediate by sympathetic nerve activity 22,34,35 . In the present study, acupuncture decreased body weight, reduced testosterone, and increased insulin sensitivity in rats with PCOS and insulin resistance, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, a woman with irregular cycles may use acupuncture to get more regular cycles and to improve PCOS-related symptoms, including health-related quality of life, mood, and insulin sensitivity, as there were few negative side effects of acupuncture. 10,11,[47][48][49][58][59][60][61] The recent RCT 18 has important clinical implications not only for women with PCOS with an active wish for pregnancy but also for those women with no active wish for pregnancy, as acupuncture induced ovulation to a higher degree than no treatment and also relieved other PCOS-related symptoms.…”
Section: Acupuncture For Infertility In Women With Pcosmentioning
confidence: 99%
“…Johansson et al [8] demonstrated that repeated acupuncture resulted in higher ovulation frequency during the treatment period in women with PCOS. In addition, acupuncture has been shown to restore dysfunctional glucose homeostasis as well as adipose tissue gene expression and DNA methylation in patients with PCOS, in part via activation of the autonomic nervous system [9]. Despite these previous findings, a recent large multicenter trial in China demonstrated that acupuncture given as a fixed protocol did not improve the live birth rate in women with PCOS when compared with placebo acupuncture or clomiphene citrate [10].…”
Section: Introductionmentioning
confidence: 96%